The Use of Realia Media in The Learning Process Can Improve Student Learning Outcomes - Kartini, Kartini (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes in mathematics lessons in elementary grade IV with mathematics media in fractional addition arithmetic operations. The research conducted is Classroom Action Research (CAR) as much as 2 cycles. The stages of each cycle are planning, implementation, observation and reflection. Each meeting was conducted pre-test and post-test to determine the progress of students. In the first cycle, the students who completed the post test were 62.5%. In cycle II, students who completed the post-test were 100%. These results indicate that through realia media, fractional addition arithmetic operations can improve fourth grade learning outcomes at SD Negeri 1 Kayuloko.